2013
DOI: 10.1007/s00464-013-3088-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cost and short-term outcomes for elderly patients in laparoscopic colonic surgery

Abstract: Combining laparoscopic colectomy with an ERP is cost-effective and results in similar short-term outcomes for the elderly and nonelderly patients. Despite higher comorbidities, elderly patients realized the same benefits of shorter LOS with similar hospital costs and readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…A number of prospective and retrospective studies have demonstrated a similar length of stay when older and younger cohorts are compared (Baek et al, 2013; Kahokehr, Sammour, Sahakian, Zargar-Shoshtari, & Hill, 2011; Keller, Lawrence, Nobel, & Delaney, 2013; Pawa, Cathcart, Arulampalam, Tutton, & Motson, 2012; Senagore et al, 2003; Verheijen, vd Ven, Davids, Vd Wall, & Pronk, 2012; Walter et al, 2011), while other studies found longer length of stay in older patients (Feroci et al, 2013; Hendry et al, 2009; Rumstadt et al, 2009). Two randomized controlled trials comparing ERAS with standard of care in elderly patients found significantly reduced length of hospital stay in patients allocated to ERAS care (Jia et al, 2014; Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…A number of prospective and retrospective studies have demonstrated a similar length of stay when older and younger cohorts are compared (Baek et al, 2013; Kahokehr, Sammour, Sahakian, Zargar-Shoshtari, & Hill, 2011; Keller, Lawrence, Nobel, & Delaney, 2013; Pawa, Cathcart, Arulampalam, Tutton, & Motson, 2012; Senagore et al, 2003; Verheijen, vd Ven, Davids, Vd Wall, & Pronk, 2012; Walter et al, 2011), while other studies found longer length of stay in older patients (Feroci et al, 2013; Hendry et al, 2009; Rumstadt et al, 2009). Two randomized controlled trials comparing ERAS with standard of care in elderly patients found significantly reduced length of hospital stay in patients allocated to ERAS care (Jia et al, 2014; Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…[10][11][12] For example, Legner and colleagues 10 noted that, in the state of Washington, surgical patients suffering complications during the index hospitalization had 2.4 times higher odds of discharge to post-acute institutional care. These studies, however, did not describe differences in use of different PAC services, nor did they report the use of PAC associated with specific operations or complications.…”
Section: Discussionmentioning
confidence: 97%
“…1). Sixteen papers were judged to be eligible: two randomized controlled trials (RCTs) [25,26], 11 cohort studies [27][28][29][30][31][32][33][34][35][36][37] and three case series [38][39][40]. There was good inter-rater agreement between reviewers (kappa score 0.896 for search, 0.882 for quality score).…”
Section: Search Outcomementioning
confidence: 99%
“…There was good inter-rater agreement between reviewers (kappa score 0.896 for search, 0.882 for quality score). Five studies were rated as good quality [30,[32][33][34][35], seven as fair quality [25][26][27]29,31,37,38] and four as poor quality [28,36,39,40] (Table S2). There was wide variation of components of ERAS protocols adopted between studies (Table S3), and no studies followed all ERAS components described by the current consensus guidelines [1].…”
Section: Search Outcomementioning
confidence: 99%